The Effect of Educational Parenting on Improvement Parenting Efficacy of Parents and Their Effects on the Language Development of Children With Down Syndrome - Upik Supiaty; Nurwijayanti; Yuly Peristiowati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Parenting self-efficacy is an important cognitive idea because it is related to the functioning of children and families. This study aims to determine the effect of parenting education on increasing parenting efficacy of parents and their impact on the language development of children with Down syndrome. This research is included in the type of experimental quantitative research with a pretest-posttest group design. The sample in this study was 30 people who were selected by the Covenience Sampling technique, namely anyone who coincidentally met the researcher could be used as a sample, if it was deemed that the person who happened to be met was suitable as a data source. The data in the study were collected by filling out a questionnaire. The collected data is then analyzed by statistical analysis. The statistical analysis in this study was carried out in 3 stages, namely: Instrument testing consisting of validity and reliability tests, Classical Assumption Test consisting of normality and homogeneity tests followed by hypothesis testing. Based on the test results, it is known that the instrument is valid and reliable and the data is normally distributed and homogeneous. The results of hypothesis testing indicate that there is an effect of parenting education on increasing parenting efficacy of parents and its impact on the language development of children with Down syndrome. After carrying out treatment as many as 16 meetings held within 4 months, it was found that there was an effect of parenting education on increasing parenting efficacy of parents and its impact on the language development of children with Down syndrome. Researchers who want to study more deeply with the same topic as this study can use a wider sample with more variables.